Improving cardiac rehabilitation uptake: Potential health gains by socioeconomic status. (November 2019) - Hinde, Sebastian; Bojke, Laura; Harrison, Alexander; Doherty, Patrick
Background: Globally, cardiac rehabilitation (CR) is recommended as soon as possible after admission from an acute myocardial infarction (MI) or revascularisation. However, uptake is consistently poor internationally, ranging from 10% to 60%. The low level of uptake is compounded by variation across different socioeconomic groups. Policy recommendations continue to focus on increasing uptake and addressing inequalities in participation; however, to date, there is a paucity of economic evidence evaluating higher CR participation rates and their relevance to socioeconomic inequality. Methods: This study constructed a de-novo cost-effectiveness model of CR, utilising the results from the latest Cochrane review and national CR audit data. We explore the role of socioeconomic status by incorporating key deprivation parameters and determine the population health gains associated with achieving an uptake target of 65%. Results: We find that the low cost of CR and the potential for reductions in subsequent MI and revascularisation rates combine to make it a highly cost-effective intervention. While CR is less cost-effective for more deprived groups, the lower level of uptake in these groups makes the potential health gains, from achieving the target, greater. Using England as a model, we estimate the expenditure that could be justified while maintaining the cost-effectiveness of CR at £68.4 m per year. Conclusions: Increasing CR uptake is cost-effective and can also be implemented to reduce known socioeconomic inequalities. Using an estimation of potential population health gains and justifiable expenditure, we have produced tools with which policymakers and commissioners can encourage greater utilisation of CR services.